Dari relasi menuju partisipasi: Sebuah teologi keterhisaban identitas manusia ke dalam imago Dei pada konteks autisme - Masnidar, Sherly (KURIOS, 2023)
This article, focusing on the theology of belongingness, centers its concern on the discriminatory interpretation of the theology of imago Dei towards individuals living with autism. Superficially, our understanding of the theology of imago Dei (image of God) legitimizes human identity as perfect creations due to their resemblance to God. Therefore, individuals living with autism are often considered outside the realm of imago Dei identity due to their limitations in physical, cognitive, and social functions. This article aims to elucidate the complexity of human identity, emphasizing that humans cannot be comprehended solely based on their physical, cognitive, and social functions. To achieve this goal, through a constructive theological approach, this article presents the participative theology of imago Dei as the fourth model of imago Dei theology, following the functional, substantial, and relational models. Ultimately, this article formulates a participative theology of imago Dei that guides us to comprehend humans' belongingness within the Imago Dei fully. Thus, we understand the essence of humanity as unrestricted by any capability reference, providing an equal space for individuals living with autism.Â AbstrakArtikel yang berfokus pada teologi keterhisaban (theology of belongingness) ini mendasarkan persoalannya pada pemaknaan teologi imago Dei yang diskriminatif terhadap orang yang hidup dengan autisme. Secara dangkal, teologi imago Dei (gambar Allah) kita pahami guna melegitimasi identitas manusia sebagai ciptaan yang sempurna karena kesegambarannya dengan Allah. Itulah sebabnya, orang yang hidup dengan autisme dianggap tidak termasuk ciptaan yang menggambarkan identitas Imago Dei karena keterbatasan fungsi fisik, kognitif, dan sosialnya. Tujuan artikel ini adalah untuk memaparkan tentang kompleksitas identitas manusia sehingga manusia tidak dapat dipahami hanya berdasarkan fungsi dan substansi fisik, kognitif, juga sosialnya. Untuk mencapai tujuan itu, melalui pendekatan teologi konstruktif, artikel ini menawarkan teologi imago Dei partisipatif sebagai model keempat teologi imago Dei, setelah model fungsional, substansial, dan relasional. Pada akhirnya, artikel ini menghasilkan teologi imago Dei model partisipatif yang menuntun kita memahami tentang keterhisaban manusia secara penuh ke dalam Sang Imago Dei. Dengan demikian, kita memahami hakikat manusia secara utuh yang tidak terikat pada acuan kemampuan apapun, sehingga ada ruang perimaan yang sama bagi orang yang hidup dengan autisme.